Residual symptoms in bipolar disorders: Findings from the bipolar Disorder course and outcome study from India (BiD-CoIN study). (August 2021) - Grover, Sandeep; Avasthi, Ajit; Chakravarty, Rahul; Dan, Amitava; Chakraborty, Kaustav; Neogi, Rajarshi; Desouza, Avinash; Nayak, Omkar; Praharaj, Samir Kumar; Menon, Vikas; Deep, Raman; Bathla, Manish; et al.
Highlights: Four-fifth (79.8%) of the patients with bipolar disorder have residual symptoms, with 53.4% having both depressive and manic residual symptoms The types of residual symptoms are related to the polarity of the most recent episode and the lifetime predominant polarity. Abstract: Aim: To explore the prevalence of residual symptoms (both depressive and manic) and their correlates in subjects with bipolar disorder in clinical remission. Methodology: This multicentric cross-sectional study included patients in clinical remission recruited across the 14 centers. The patients were evaluated on the Hamilton Depression Rating Scale (HDRS) and Young Mania Rating Scale (YMRS) for the prevalence of residual symptoms. A score of ≤7 on both scales defined the presence of residual symptoms. Results: Four-fifth (79.8%) of the participants had residual symptoms, with 130 (16.8%) having only residual depressive symptoms, 74 (9.6%) having only residual manic symptoms, and 413 (53.4%) having both depressive and manic residual symptoms, on HDRS and YMRS. The residual symptoms were related to the polarity of the most recent episode and the lifetime predominant polarity. Higher numbers of lifetime depressive episodes are associated with higher residual depressive symptoms, and higher numbers of lifetime manic episodes are associated with higher chances of having residual manic symptoms. Conclusions: A large proportion of patients with bipolar disorder have residual symptoms during the remission phase. Clinicians need to make efforts to identify and address the same to improve the treatment outcome.